The Influence of Financial and Environmental Performance on Stock Prices: Evidence from Indonesian Manufacturing Firms - Feinnudin, A Agung; Wahono, Puji (Journal of Economics and Management Scienties, 2025)
This study examines the influence of financial and environmental performance on stock prices among manufacturing companies listed on the Indonesia Stock Exchange during the period 2015–2024. Using panel data regression with the Random Effect Model (REM), the results show that Return on Assets (ROA), Net Profit, and Greenhouse Gas (GHG) Emissions have significant positive effects on stock prices, while Return on Equity (ROE) does not have a significant impact. These findings highlight those financial fundamentals remain the primary determinants of stock price movements, while environmental performance is beginning to serve as an indirect indicator of firm size and strength. The study suggests that investors in emerging markets continue to prioritize profitability and operational efficiency, although sustainability considerations are gradually gaining relevance. Future research is recommended to incorporate firm size controls and ESG quality measures to deepen the understanding of sustainability’s role in market valuation.